Clinical determinants of weight loss in patients receiving radiation and chemoirradiation for head and neck cancer: A prospective longitudinal view. Issue 5 (22nd June 2012) - Kubrak, Catherine; Olson, Kärin; Jha, Naresh; Scrimger, Rufus; Parliament, Matthew; McCargar, Linda; Koski, Sheryl; Baracos, Vickie E.
Abstract Background We aimed to determine the effects of systemic inflammation and symptoms of head and neck cancer patients on dietary intake and weight in relation to mode of treatment. Methods In all, 38 orally fed patients had intake, weight, C‐reactive protein (CRP), and symptoms prospectively assessed at baseline, post‐treatment, and follow‐up. Results Intake/weight declined and CRP increased substantially in chemoirradiation patients (−11.4 ± 5.2 kg, −1214 kcal/day, 23.4 ± 24.9 mg/L; p < .05) versus radiotherapy patients (−3.5 ± 4.8 kg, −483 kcal/day, 8.3 ± 13.9 mg/L) during posttreatment (repeated‐measures ANOVA). Multivariate generalized estimating equations modeling identified reduced swallowing capacity was a key predictor of energy intake in both treatment groups (p < .001); multiple symptoms experienced by radiotherapy/chemoirradiation patients were significant predictors of weight loss; additionally, in chemoirradiation patients, CRP was an independent predictor of weight loss (p < .001). Conclusions Treatment of symptoms and systemic inflammation are important clinical targets to manage weight loss in patients with head and neck cancer, especially those treated with chemoirradiation. Head Neck, 2013